Effects of nitrogen level on purslane antioxidant activity - de Jesus, Sofia (2019)
The high antioxidant activity of purslane, Portulaca oleracea, gives it a high nutritional and functional value. The commercial production of purslane has increased in Portugal, giving rise to the need for finding out the effects of inputs, mainly nitrogen, on antioxidant activity. Αn experiment with four levels of N application (0, 30, 60 and 90 kg N ha-1) was carried out. Golden-leaf purslane plants were grown in styrofoam boxes filled with substrate and were fertigated twice a week, over four weeks, with ammonium nitrate solution (16.9% NO3--N and 16.7% NH4+-N). Increase in nitrogen level led to decrease in water-soluble proteins content. However, ascorbic acid and phenols content, as well as antioxidant activity measured by the FRAP method, were not affected by nitrogen level. Shoot antioxidant activity, measured by the DPPH method was lower at 90 kg N ha-1 (26.20 mg GAE g-1 FW). On the other hand, shoot antioxidant activity mediated by peroxidases was higher at 30 kg N ha-1 treatment (0.459 µmol min-1 mg-1 prot.). The application of 60 kg N ha-1 allowed a vigorous plant growth without disturbing antioxidants and conservation properties.